Effects of heterogeneity on the ecological diversity and redundancy of forest fauna - Heidrich, Lea; Brandl, Roland; Ammer, Christian; Bae, Soyeon; Bässler, Claus; Doerfler, Inken; Fischer, Markus; Gossner, Martin M.; Heurich, Marco; Heibl, Christoph; Jung, Kirsten; Krzystek, Peter; et al. (Basic and applied ecology, 2023)
Heterogeneity in forests might promote biodiversity not only through an increase in niche volume but also through other processes, such as an increase in resources and their spatial distribution. However, negative relationships between heterogeneity and biodiversity have also been observed, which may indicate that heterogeneity acts as a filter for some species. This study examined the effects of different facets of heterogeneity in forest stands, i.e. deadwood, plant diversity, forest stand structure, and micro-scale topography, on the ecological (functional-phylogenetic) diversity and redundancy of nine animal groups: moths, true bugs, different functional groups of beetles, spiders, birds, and bats. Overall, we found positive effects of heterogeneity on ecological diversity and redundancy. Although the effect of heterogeneity at the local scale was moderate compared with the general effect of region, greater heterogeneity could be beneficial to some species groups and lead to more resilient species communities.